Fabrication, Physico-Chemical, and Pharmaceutical Characterization of Budesonide-Loaded Electrospun Fibers for Drug Targeting to the Colon. Issue 11 (November 2015) - Bruni, Giovanna; Maggi, Lauretta; Tammaro, Loredana; Canobbio, Andrea; Di Lorenzo, Rosadele; D'aniello, Sharon; Domenighini, Chiara; Berbenni, Vittorio; Milanese, Chiara; Marini, Amedeo
ABSTRACT: The objective of this study was to fabricate and characterize electrospun fibers loaded with budesonide with the aim of controlling its release in the gastrointestinal tract. Budesonide is a nonhalogenated glucocorticosteroid drug, highly effective in the treatment of some inflammatory bowel diseases with local action throughout ileum and colon. At this aim, Eudragit® S 100, a polymer soluble at pH > 7, commonly used for enteric release of drugs, has been successfully spun into ultrafine fibers loaded with Budesonide (B) at 9% and 20% (w/w) using the electrospinning process. The physico-chemical characterization by scanning electron microscopy, X-ray diffraction, FTIR spectroscopy, and thermal analyses indicated the amorphous nature of budesonide in the electrospun systems. Dissolution rate measurements using a pH-change method showed negligible drug dissolved at pH 1.0 and sustained release at pH 7.2. Therefore, the pharmaceutical systems proposed, made of fibers, represent an effective method for drug targeting to terminal ileum and colon with the aim of improving the local efficacy of this drug.